SPANISH ORIENTAL SCHOOL - Shukr Al-Mahdawi, Huda Nouri (Revista Inclusiones, 2021)
In Islamic history, it is traditionally considered that Spanish Orientalism is the first European study of the East, which was started in the colonial era between the 18th and 19th centuries. Orientalism was created by the Spanish world to study the countries of the East in the following directions: history, economics, geography, language, literature, anthropology, arts, religions, philosophy, archeology. Its purpose is the subordination and control of the Eastern world in accordance with the objectives of the European countries. It is divided into three main stages: colonial, post-colonial and the new Orientalism. The effects of Spanish Orientalism can be divided into positive – the dissemination of Islamic heritage, the transfer of Islamic and Oriental knowledge in general to the West, the evolution of the critical mental approach in the West, the coloring of the literary and artistic movement in the West in an oriental tone, and the negative effects – the colonial, commercial, political, scientific, religious controls.